Disc inflammation and intercellular communication in shaping the immune microenvironment of intervertebral disc degeneration - Wei, Mengcheng; Zhu, Kanghua (Frontiers in Immunology, 2025)
BackgroundIntervertebral disc degeneration (IDD) is a major cause of low back pain, significantly affecting the quality of life of elderly individuals worldwide. Its pathogenesis is complex, involving extracellular matrix degradation, inflammatory responses, and immune regulation.MethodsThis study integrated multiple transcriptomic and single-cell RNA-seq datasets, and systematically identified and validated key IDD-related genes and their immune regulatory roles through differential gene analysis, GO/KEGG enrichment, PPI network construction, ANN, LASSO, random forest, SVM-RFE, SHAP, Mendelian Randomization, as well as immune cell infiltration and CellChat analyses. The identified candidate genes were further validated experimentally using Western blot, confirming their expression patterns and potential as diagnostic biomarkers.ResultsBy integrating bioinformatics with in vitro validation, this study identified three key biomarkers associated with IDD: MMP9, HPGD, and UCHL1. SHAP analysis demonstrated that these genes make significant contributions to the diagnostic model, primarily participating in immune regulation and inflammatory responses. Functional enrichment analysis indicated their involvement in signaling pathways such as IL-17, TNF, and MAPK. Correlation and differential analyses of immune cells showed that γδ T cells exhibited significant changes across all three genes, while other immune cell types, such as CD4⁺ T cells, displayed differences in the remaining biomarkers. Single-cell analysis further revealed that the MIF signaling pathway plays a key role in the interactions between nucleus pulposus cells and immune cells.ConclusionThese findings provide new insights into the molecular and immune mechanisms of IDD and offer potential targets for diagnosis and therapy.